2016
DOI: 10.1159/000443422
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C is Associated With Plaque Phenotype and Plaque Burden

Abstract: Background/Aims: The relationship between carotid artery plaque burden, phenotype and serum cystatin C at normal and impaired renal function is still unclear. Methods: Demographic characteristics, carotid ultrasonography and other relevant information of 1,477 patients were collected. The association of carotid artery plaque burden, plaque phenotype with serum cystatin C was evaluated by strategy analysis based on renal function. Results: Serum cystatin C (OR=2.05, 95% CI: 1.83-2.29, P<.01) was a risk factor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Since biomarkers are proposed for risk stratification due to their relative ease of use, high-sensitivity cardiac troponin T (hs-cTnT) [ 11 13 ], NT-proBNP [ 14 ], Cystatin C [ 15 ], serum matrix metalloproteinase-9 [ 16 ], and lipoprotein-associated phospholipase A2 [ 17 ] have been considered closely related with coronary plaque morphology. Of note, a recent study revealed that the low-density lipoprotein-cholesterol/high-density lipoprotein-cholesterol (L/H) ratio independently had a significant fixed effect with the percentage of the lipid component of coronary plaques [ 18 ] and a high L/H ratio was reported closely associated with larger numbers of low density noncalcified plaque [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since biomarkers are proposed for risk stratification due to their relative ease of use, high-sensitivity cardiac troponin T (hs-cTnT) [ 11 13 ], NT-proBNP [ 14 ], Cystatin C [ 15 ], serum matrix metalloproteinase-9 [ 16 ], and lipoprotein-associated phospholipase A2 [ 17 ] have been considered closely related with coronary plaque morphology. Of note, a recent study revealed that the low-density lipoprotein-cholesterol/high-density lipoprotein-cholesterol (L/H) ratio independently had a significant fixed effect with the percentage of the lipid component of coronary plaques [ 18 ] and a high L/H ratio was reported closely associated with larger numbers of low density noncalcified plaque [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of previous studies had reported that cystatin C level was superior to many biomarkers studied for identifying patients with subclinical atherosclerosis as defined by arterial wall elas ticity [6] . Other studies had reported a significant association between serum cystatin C level and carotid atherosclerosis as assessed by maximum carotid plaque thickness [7] or by atherosclerotic plaque burden [8] . Additionally, a study had reported that cystatin C level was a strong and independent predictor of overall mortality as well as mortality and morbidity from CVD among the elderly [9] .…”
Section: Discussionmentioning
confidence: 97%
“…Plasma CysC levels are strongly associated with an increased risk of CAD, particularly for secondary CAD events 28 , 29 , 38 ) . Wen et al have reported the relationship between serum CysC levels and the presence of a carotid plaque 30 ) . Therefore, serum CysC and intracellular CysC should have different functions in atherosclerotic mechanisms, i.e., serum CysC may cause a reduction in serum APN clearance and suppress the vasculoprotective effects of APN through the formation of the CysC–APN complex, which can explain the paradox that hyperadiponectinemia is associated with increased CAD risk in patients with renal impairment 39 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum CysC levels indicate an increasing risk for cardiovascular events in subjects regardless of renal dysfunction 28 , 29 ) . We have previously reported that CysC reduces the clearance of plasma APN, leading to the inhibition of APN-mediated vasculoprotective effects 19 ) , and a recent report has demonstrated that serum CysC levels might be linked to carotid plaque size and instability 30 ) . However, the clinical significance of the CysC–APN complex on plaque vulnerability is still unknown.…”
Section: Introductionmentioning
confidence: 99%